Reverse transcription and polymerase chain reaction: principles and applications in dentistry Transcrição reversa e reação em cadeia da polimerase: princípios e aplicações em odontologia - Carlos Ferreira dos Santos; Vivien Thiemy Sakai; Maria Aparecida de Andrade Moreira Machado; Daniela Nicole Schippers; Andrew Seth Greene (University of São Paulo, 2004)
Various molecular biology techniques have become available in the last few years. One of the most revolutionary of these techniques regarding nucleic acid analysis is the polymerase chain reaction (PCR), which was first described in 1985. This method relies on the exponential amplification of specific DNA fragments, resulting in millions of copies that can serve as templates for different kinds of analyses. PCR can be preceded by a reverse transcription (RT) reaction in order to produce cDNA from RNA (RT-PCR). RT-PCR provides the possibility to assess gene transcription in cells or tissues. PCR and RT-PCR techniques have been instrumental in dental research, and show potential to be used for diagnosis as well as for treatment and prevention of many diseases (dental caries, periodontal disease, endodontic infections and oral cancer). Compared to other traditional methodologies, PCR and RT-PCR show many advantages including high specificity, sensitivity, and speed. Since PCR and RT-PCR are relatively new techniques and are not available to most students and professionals involved with dentistry, the aim of this work is to present the details of these techniques as well as dental literature reports in which they were used. Várias técnicas de biologia molecular têm sido disponibilizadas nos últimos anos. Uma que revolucionou a análise de ácidos nucléicos foi a reação em cadeia da polimerase (PCR), descrita pela primeira vez em 1985. Esta técnica baseia-se na possibilidade de amplificação exponencial de fragmentos específicos de DNA, com a criação de milhões de cópias que servirão como matéria-prima para diferentes tipos de análises. A PCR pode ser precedida por uma reação de transcrição reversa (RT) para a obtenção de cDNA a partir de RNA (RT-PCR), representando, por exemplo, uma possibilidade de análise de expressão gênica em células ou tecidos. As técnicas de PCR e RT-PCR têm sido utilizadas em pesquisas odontológicas como ferramentas auxiliares para nortear não só o diagnóstico como também o tratamento e prevenção de várias doenças (cárie, doença periodontal, lesões endodônticas e câncer), uma vez que se mostram vantajosas em comparação a outras técnicas tradicionais pela sua alta especificidade, alta sensibilidade e rapidez. Por se tratar de técnicas relativamente novas e não disponíveis para a maioria dos profissionais e estudantes de Odontologia, o objetivo do presente trabalho é apresentar detalhes da PCR e da RT-PCR, bem como trabalhos da literatura em que ambas foram utilizadas.